2010
DOI: 10.1016/j.jpainsymman.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Families' Perceptions of Veterans' Distress Due to Post-Traumatic Stress Disorder-Related Symptoms at the End of Life

Abstract: PTSD-related symptoms may be common and severe among veterans near the end of life and may have a negative effect on families' perceptions of the quality of care that the veteran received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…As an example, it is common for patients who experienced trauma to have increased agitation, pain, and dyspnea at end of life. 17 Thus, opportunities to investigate the impact of prior maltreatment on serious illness at end of life are needed, which might include a longitudinal examination of pediatric health data in foster care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, it is common for patients who experienced trauma to have increased agitation, pain, and dyspnea at end of life. 17 Thus, opportunities to investigate the impact of prior maltreatment on serious illness at end of life are needed, which might include a longitudinal examination of pediatric health data in foster care.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma has been shown to increase agitation, pain, and dyspnea at end of life. 17 It may also negatively influence quality of life and daily functioning. 18 Trauma may increase the intensity of burdensome symptoms, treatments, or caregiver stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that up to 17% of veterans receiving HPC are diagnosed with post-traumatic stress disorder (PTSD) 36 , and generally, veterans present with higher rates of trauma-related disorders at end-of-life than civilians. 24 Further, scholars expect these figures to rise as Vietnam-era veterans experience higher rates of PTSD and other psychiatric disorders compared to previous cohorts.…”
Section: Mental Healthmentioning
confidence: 99%
“…In addition, previous research suggests that families of patients with PTSD report lower satisfaction with VA HPC. 36 Therefore, barriers to mental health treatment associated with masculinity and military culture may lead to particularly negative outcomes for older male veterans with PTSD.…”
Section: Mental Healthmentioning
confidence: 99%
“…9 Although a systematic review concluded that delayed-onset PTSD is unusual, especially in the absence of prior symptoms, 10 PTSD can first appear or worsen in old age. 11,12 In particular, symptoms may emerge or reemerge as individuals approach death, possibly due to challenges that arise during the aging process (e.g., increased health problems, cognitive decline, loss of loved ones). 13,14 In addition, thoughts about impending mortality may trigger reminders of traumatic experiences and memories.…”
mentioning
confidence: 99%